The effect of UV-C in combination with H2O2 treatments on microbial response and quality parameters of fresh cut pear discs - Schenk, Marcela Liliana (2012)
The response of Escherichia coli ATCC 11229, Listeria innocua ATCC 33090 and Zygosaccharomyces bailii NRRL 7256 in fresh-cut pear to simultaneous and serial combined treatments involving H 2O 2 immersion (3% w/v; pH 3.0; 25°C; 2.0 or 5.0min) and UV-C exposure (7.5min; 3.7kJm -2) was investigated. For selected treatments, native flora, sensory and colour changes were also evaluated. E. coli and L. innocua were more sensitive than Z. bailii. Serial H 2O 2/UV-C treatments were more effective than the simultaneous arrangement. The single effect of UV-C was enhanced by the combination with 5min H 2O 2, hence avoiding the recovery of the surviving population. The combined treatment kept optimal microbial stability and exhibited more luminosity than the single UV-C treatment. Texture profile analysis conducted using a trained panel showed that H 2O 2/UV-C processed pear discs were perceived with significantly less hardness and fracturability but as juicy as untreated discs. Consumers found them pleasant.